Students and higher education institutions relationship: emotional commitment, loyalty and love brand - Carvalhal, Breno; Almeida, Luciana Florêncio De; Bruno Henrique De Araujo (Retail Management Review, 2023)
Objective: The present research purpose consisted of investigate the strength of social and academic integration, perceived quality and trust to emotional commitment to Higher Education Institutions (HEI) and its relationship with loyalty, as well as testing the impact of loyalty to HEI on brand love Methodology: A survey method was applied with undergraduate students from a private HEI (named here as ALPHA) with 3 campuses located in São Paulo, Rio de Janeiro and Porto Alegre, totaling 306 valid questionnaires. Originality: The novelty consisted of replicate an adapted version of the RQSL model using only variables with high predictive power as presented in previous research. Additionally, the brand love construct was added as outcome of the student loyalty. The results demonstrated that the adaptation proved to be a reliable predictive instrument to explain that the students’ loyalty to a private HEI is strongly linked to their emotional commitment. Main results: The research showed the strength of three antecedents in the construction of students’ emotional commitment to HEI, namely: social and academic integration, perceived quality and trust. Brand love emerged as a significant outcome of student loyalty to a HEI. In this sense, the greater the emotional commitment, the greater the student’s loyalty and, consequently, the greater brand love to the HEI. Theoretical Contributions: The results showed that among the four antecedent factors, social integration has a significant force. In this sense, one might consider that feeling of participation in the group and the sense of belonging are considered of great importance by the students, in addition to factors such as quality, trust and academic integration.